Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. The Perspectives of Parents of Primary School Students in the City of Amman about their Children’s Use of the Moodle and the Obstacles they faced while using it Prof. Khalid Ibrahim Ajlouni , Mrs. Amani Mohammed Ahmad Ameerah 2. Teaching Practices of Mathematics Teachers in Developing Probe Thinking Dr. Turki Humaid Alsulami 3. Self-learning skills included at family education for intermediate school Mrs. Amal Asir Ayed Al-Otaibi, Prof. Latifa Salih Al-Sumairi 4. E-educational platforms and their role in achieving school reform from the teacher’s Perspectives in light of the distance education experience (Madrasati platform as a model) Co-Prof. Rofaydah Adnan Al-Ansary 5. Analyzing the Content of Physics Books in Light of Visual Thinking Skills Mrs. Hanan Mohammad Abdullah Al-Tamimi, Dr. Latifa Mohammad Rasheed Al-Mushaigeh 6. The Impact of Narrative Method Used to Improve Some Skills of Reading Aloud Related to 5th Grade Students in Medina Area Mr. Muhammad Saeed Aljuhani 7. Investigating the impact of Learning English as a foreign language on creative writing skills amongst gifted secondary students in national and international private Schools in Alhasa (A case study) Mrs. Albandary Abdullah Alhassan